A COMPARATIVE ANALYSIS OF QUALITY OF LIFE AMONG INDIVIDUALS WITH OPIOID AND ALCOHOL DEPENDENCE SYNDROMES - Dr. Aditya Soni; Dr. Devanshi Tripathi; Dr. Rujul Modi; Dr. Manju Bhaskar (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Background and Objectives: Substance use disorders, particularly those involving alcohol and opioids, significantly impact individuals’ quality of life (QoL), affecting physical, psychological, social, and environmental domains. Both alcohol and opioid dependence syndromes (ADS and ODS) lead to considerable morbidity and mortality, but their effects on QoL vary due to differences in pharmacological properties and social consequences. This study aims to compare the QoL in patients with ADS and ODS, highlighting specific life aspects more adversely affected by each disorder. Understanding these differences will inform tailored interventions, improve public health strategies, and enhance support services, contributing to better management and rehabilitation of individuals with SUDs.Materials and Methods: This cross-sectional study, conducted at the Department of Psychiatry, Mahatma Gandhi Medical College and Hospital, Jaipur, Rajasthan, included 100 participants: 50 diagnosed with ADS and 50 with ODS, as per ICD-10 criteria. All participants met the study's inclusion and exclusion criteria. Sociodemographic and clinical characteristics were assessed using a sociodemographic proforma, and the WHOQOL-BREF scale was used to evaluate their QoL.Results: The majority of patients were men (96%), with mean ages of 34.7 years (ADS) and 32.0 years (ODS). Statistically significant differences in QoL scores were observed between ADS and ODS patients across WHOQOL-BREF domains: physical (ADS: 63.7, ODS: 48.6), psychological (ADS: 63.7, ODS: 37.1), social relationships (ADS: 69.3, ODS: 38.6), and environment (ADS: 74.9, ODS: 51.3), with p-values < 0.0001. Gender and family type influenced QoL in ADS patients, while no sociodemographic parameters influenced ODS patients.Conclusion: Substance use disorders negatively impact QoL, with opioid use disorder having a more severe effect. Comprehensive, tailored treatment is essential for addressing the unique challenges of each group.